Pengembangan Media Pembelajaran ARDI (AR-Digital Book) Berbasis Augmented Reality 3D Animated Pada Materi Induksi Elektromagnetik (IPF: Inovasi Pendidikan Fisika, 2023)
This study aims to produce and develop ARDI digital books on the physics of electromagnetic induction. The research method used is research and development with the ADDIE development model, but limited use of ADD, namely Analysis, Design, and Development. ARDI digital books were validated by 5 (five people), namely 1 IT expert, 2 physicists, and 2 learning media experts. The analysis consists of selecting topics, analyzing the physics of electromagnetic induction and analyzing learning media. The design features 3D animation designs using Blender 3.4 software and augmented reality using Meta Spark Studio and Player. Development contains the development of a 3D animation design presented in the form of a digital book which can be accessed through the playstore or appstore. Furthermore, the trial results data were analyzed descriptively and the expert validation results data were analyzed using the content validity ratio (CVR). The results showed that the results of the validation of the ARDI design that had been made feasible were developed with the responses of all validators giving a value of 1 (one) in 4 (four) aspect items being assessed. From the research conducted, it can be concluded that ARDI learning media which describes the physics of electromagnetic induction is suitable for use as a new medium, the drawbacks of ARDI media are that it does not yet provide gamification and virtual laboratories that require additional presentation of physics concepts. The recommendations given for further research are the development of gamification and virtual laboratories in ARDI digital books